Impact on food chain due to the reduction in population of Indian House Sparrows - B, Leelesh Sundaram. (International Journal of Psychosocial Rehabilitation, 2020)
Due to various human activities including changes in the life style of human and overall industrial development have led to reduction of the population of the Indian house sparrows. As the environment is linked with one and other a natural ambiguity arises with respect to the impact caused in the food chain; sparrows occupy an indispensible role in the food chain, a sudden fall in the population of a particular species would definably affect the same. Thus, the study aims to identify the impact caused in the food chain due to the reduction in population of Indian house sparrows. The reduction in the population of Indian house sparrows can be traced only in current decade, so inorder to trace the impact on food chain the awareness of individuals from different age groups are taken into account, as the targeted respondents are the witnesses for the fall above change. By virtue of simple random sampling with sample size of 1513, using correlation, chi-square and symmetric measures test, it was found out that due to reduction in population of Indian House sparrows there is an adverse impact is created on the food chain. Since there is a reduction in population of Indian house sparrows, it creates an impact over the plant life, the plants and crops such as grass, thorn, and weeds. There is a rapid increase in the population of insects and worms. The size of hawks and snakes has reduced. The study recommends that the government must carry out captive breeding process for protecting the Indian House sparrows